Naruto: A Study of Resilience and Growth in Japanese Animation - Rosyidha, Alfin; Rohmah, Naila (KIRYOKU, 2025)
Resilience is a fundamental psychological trait that enables individuals to overcome difficulty and grow stronger through challenges. Naruto, one of the most influential Japanese anime series, presents a compelling portrayal of resilience through its protagonist, Naruto Uzumaki. This study explores Naruto as a narrative model of resilience, analysing his character development through psychological, cultural, and narrative frameworks. Drawing upon post-traumatic growth theory, the Hero’s Journey, and Japanese cultural values, this research examines how Naruto’s journey—from an outcast to a respected leader—exemplifies emotional intelligence, perseverance, and adaptive coping mechanisms. The findings suggest that Naruto provides a unique representation of resilience as a dynamic and socially influenced process, shaped by mentorship, emotional regulation, and a strong sense of purpose. Furthermore, the global appeal of Naruto underscores the universal relevance of resilience narratives, demonstrating how anime serves as a powerful medium for psychological and cultural storytelling. By bridging psychological theories with anime studies, this research contributes to a deeper understanding of how media influences personal development and social identity across cultures.